POST THYROIDECTOMY COMPLICATIONS: THE HYDERABAD EXPERIENCE - Khanzada, Tariq Wahab; Samad, Abdul; Memon, Waseem; Kumar, Basant (Journal of Ayub Medical College Abbottabad, 2010)
Objective: Thyroidectomy is a very common surgical procedure worldwide and is performed by surgeons with varied training. The outcome and complication rates are largely dependent on surgeon’s skill and experience, the extent of surgery, indication of surgery and number of thyroid surgeries performed at that particular centre. The objective of this study was to determine the frequency of postoperative complications after thyroid surgery in Hyderabad, Pakistan. Study Design: It was a descriptive study and was carried out at 2 private hospitals including a teaching University Hospital over a period of 3 years from April 2005 to March 2008. Patients and Methods: All patients with goitre, who underwent any sort of thyroid surgery, were included in this study. Patients’ bio-data including name, age sex, clinical status of thyroid, thyroid function tests, ultrasound, fine needle aspiration cytology and operative procedure, findings, post operative complications and histopathology reports were recorded. Data were analysed using SPSS 16.0. Results: The overall postoperative complication rate was 10.7%. Postoperative hypocalcaemia was the most frequent complication observed in 3.5% of all patients followed by recurrent laryngeal nerve (RLN) injury noted in 2.8% patients. The less common complications were bleeding, seroma formation and wound infection. Majority of these complications were associated with total thyroidectomy, male gender, and in patients with age more than 30 years. Conclusion: The commonest post thyroidectomy complication was hypocalcaemia. Male gender, old age, and extensive thyroid surgery were associated with increased complication rate. Keywords: thyroidectomy, hypocalcaemia, recurrent laryngeal nerve injury